Expression levels of elastin and related genes in human varicose veins - (:unkn) unknown (My University, 2014)
Among the suspected reasons for varicose vein formation are changes in the quantity and content of the elastin protein; however, comprehensive investigations about elastin assembly in varicose vein formation are yet lacking. In this study, we aimed to determine the changes in mRNA levels of elastin and some of its functionally related proteins, fibulin 5, LOXL-1, MMP-2 and MMP-9 in varicose vein formation. We analysed the mRNA levels of elastin, fibulin-5, LOXL1, MMP2 and MMP9 in samples of 35 healthy and 35 varicose great saphenous vein tissues. mRNA levels of these genes were determined by using real-time PCR and normalized with HPRT1. When we compared the patient and control groups, elastin mRNA levels were significantly higher in the patient group than in the control group (P = 0.047), although there were no significant differences in fibulin 5, LOXL1, MMP2 and MMP9 mRNA levels between the patient and control groups. We showed that up-regulation of MMP2 mRNA expression was significantly correlated with hyperlipidaemia (P = 0.029). The up-regulation of elastin expression may play an important role in the pathogenesis of primary varicose veins. Additionally, the up-regulation of MMP2 expression was strongly correlated with hyperlipidaemia in varicose veins.
Keywords: Female; Humans; Middle Aged; Aged; Male; Extracellular Matrix Proteins; In Vitro Techniques; Varicose Veins; Matrix Metalloproteinase 2; Amino Acid Oxidoreductases; Elastin